Nutrient Management in Spring Rice (Oryza sativa L.) at Gauradha, Jhapa, Nepal - Ghimire, Sadikshya; Lamsal, Ganesh; Bhattarai, Sony; Ghimire, Suman (Journal of the Institute of Agriculture and Animal Science, 2025)
Rice is a major crop in eastern Nepal but the huge yield gaps were recorded and nutrient management ranked the major reasons behind it. A field experiment was carried out in Nepal Polytechnic Institute, in eastern Nepal during the spring of 2023 to evaluate the effect of different nutrient management practices on growth and yield of spring rice (Oryza sativa L. cv. Hardinath-1). Altogether six treatments: T1: Farmers' practice (150:50:25 NPK kg/ha), T2: Phosphorus only (50 kg/ha), T3: Nitrogen only (150 kg/ha), T4: Potassium only (40 kg/ha), T5: Government recommendation with FYM+NPK (15 t/ha FYM + 150:50:40 NPK kg/ha), and T6: NPK only (150:50:40 NPK kg/ha) were allocated in Randomized Complete Block Design (RCBD) with four replications. With regard to plant height (96.89 cm), number of tillers (463.57/m2), grains per panicle (170), and grain production (7.08 t/ha), the Government-recommended FYM + NPK treatment performed noticeably better result, whereas the Phosphorus-only treatment showed the lowest values. Hence, rice cultivation with integrated nutrient management i.e. government recommended FYM together with NPK (15 t/ha FYM + 150:50:40 NPK kg/ha), is a promising practice and has to be promoted in similar agro-ecological zones to maximize the rice productivity in Nepal.